2019
DOI: 10.1021/acs.inorgchem.8b02889
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Bonding Mechanism of Selenium Nitrides

Abstract: The high-pressure phase diagrams of binary Se–N system have been constructed using the CALYPSO method and first-principles calculations. Four stable compounds (Cmc21-SeN2, P21 /m-SeN3, P1̅-SeN4, and P1̅-SeN5) were identified at high pressures. Various peculiar nitrogen polymerization forms composed of single/double nitrogen–nitrogen bonds were found at the nitrogen-rich condition, such as N∞-chains in P21/m-SeN3, oligomeric N8-chains in P1̅-SeN4, and distorted N6 3– anion rings in P1̅-SeN5. Peculiar nitrogen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
(93 reference statements)
1
13
0
Order By: Relevance
“…As the isovalue values of ELF are set as 0.8, no electron localization state is observed around the Mn atom, which indicates a weak ionic bond interaction between the Mn and N atom. 72 This is also in good agreement with the analysis of PDOS that little hybridization is observed between the Mn_3d and N_2p orbitals. In contrast, the large electron localization state between the N atoms means a strong N–N covalent bond interaction.…”
Section: Resultssupporting
confidence: 88%
“…As the isovalue values of ELF are set as 0.8, no electron localization state is observed around the Mn atom, which indicates a weak ionic bond interaction between the Mn and N atom. 72 This is also in good agreement with the analysis of PDOS that little hybridization is observed between the Mn_3d and N_2p orbitals. In contrast, the large electron localization state between the N atoms means a strong N–N covalent bond interaction.…”
Section: Resultssupporting
confidence: 88%
“…3c,d In that context investigations of the high-pressure phase diagrams of the binary selenium-nitrogen system by Cui and co-workers reported in 2019 are of considerable interest. 52 These authors identified four stable compounds at high pressures: Cmc2 1 -SeN 2 , P2 1 /m-SeN 3 , P1-SeN 4 and P1-SeN 5 . As illustrated in Fig.…”
Section: Nitrogen-rich Selenium Nitridesmentioning
confidence: 99%
“…9, these novel nitrogen-rich materials are predicted to incorporate a variety of polynitrogen arrangements in the solid state. 52 The binary selenium nitride Cmc2 1 -SeN 2 has a layer structure ( Fig. 9a), while P2 1 /m-SeN 3 , P1-SeN 4 and P1-SeN 5 incorporate N ∞ -chains ( Fig.…”
Section: Nitrogen-rich Selenium Nitridesmentioning
confidence: 99%
See 1 more Smart Citation
“…At ambient conditions, the chemical energy released by the NF- Cmca phase is 1.84 eV/fu . The energy density of NF is compared to that of other reported nitrides AN x (A = B, H, Se, and S), which share the property of covalent bonds between element A and nitrogen, as shown in Figure . Although NF has the lowest nitrogen fraction, its gravimetric energy density of 5.38 kJ/g is the highest among these compounds, surpassing that of TNT (4.30 kJ/g) and edging closer to HMX (5.70 kJ/g) .…”
mentioning
confidence: 99%